201 CYTOSOLIC CALCIUM AND ZINC IN CARDIOMYOCYTES OF RATS WITH ALDOSTERONISM: RESPONSE TO SPIRONOLACTONE AND AMLODIPINE COTREATMENT. Issue 1 (1st January 2007) - Deshmukh, P. A.; Kamalov, G.; Bhattacharya, S. K.; Ahokas, R. A.; Sun, Y.; Weber, K. T.
Abstract : Purpose: Aldosterone/salt treatment (ALDOST) is associated with increased urinary losses of Ca 2+ and Zn, which can be prevented by spironolactone (S), an aldosterone receptor antagonist. The hypercalciuria and hyperzincuria of aldosteronism lead to hypocalcemia and the appearance of secondary hyperparathyroidism and to hypozincemia. Parathyroid hormone (PTH) promotes intracellular Ca 2+ overloading in diverse tissues, including the myocardium. In addition, aldosteronism is associated with increased expression and activity of cardiomyocyte L-type Ca 2+ channels. We hypothesized that aldosteronism leads to increased cardiomyocyte cytosolic [Ca 2+ ]i and is accompanied by increased cytosolic [Zn 2+ ]i, which could be prevented by S or attenuated by a Ca 2+ channel blocker. Methods and Results: Cardiomyocytes were harvested by retrograde collagenase perfusion of the isolated, crystalloid-perfused rat heart. Cells were loaded in the dark with a Ca 2+ (Fura-2)- or Zn (FluoZin-3)-sensitive fluorescent probe for 1 hour with fluorescence measured, respectively, with a spectrophotometer or flow cytometer. Only viable cells deesterify Fura-2 into its active form; cell membrane integrity, a marker of cell viability, was determined by propidium iodide labeling. Four experimental groups were studied: age-/gender-matched controls (C); 4 weeks aldosterone (0.75 μg/h by minipump) + 1% NaCl in drinking water (A); 4 weeks A + S (150 mg/kg/d by gavage); and 4 weeks A + amlodipine (CCB, 5 mg/kg/d by gavage). We found ( p < .05: *A versus C, † A + S versus A, ‡ A + CCB vs A; mean ± SEM): Conclusions: Cardiomyocyte [Ca 2+ ]i and [Zn]i each rose in response to aldosteronism. In the case of Ca 2+, this occurred via Ca 2+ channel entry, which could be blocked by either S or CCB but which do not discriminate between PTH-mediated or increased L-type channel expression. In the case of Zn, a CCB attenuated but did not prevent the rise in [Zn]i, suggesting that Zn transporters are also involved in its entry. The functional significance of Ca 2+ and Zn loading of cardiomyocytes in aldosteronism now needs to be addressed and may adversely affect the heart's electrical behavior and antioxidant defenses.